Pnrsv- An Emerging Challenge for Temperate Fruit Production (Journal of Plant Disease Sciences, 2018)
Commercial temperate fruits of Himachal Pradesh (apple, peach, pear, plum, apricot, cherry, almond, and nectarine) were visually indexed between 2015 and 2017 at regular intervals in different orchards of Shimla, Solan, Sirmour, Kullu and Kinnaur districts of the state. The variations of symptoms exhibited in different cultivars of these temperate fruit crops while indexing the plants visually. Samples were drawn from the infected plants and brought to the laboratory for serological confirmation of the virus status of infected plants. Since prunus necrotic ringspot virus (PNRSV) is a latent virus and mere presence of symptoms cannot be considered as the sole criteria for establishing the identity of this virus in temperate fruit crops. DAS-ELISA proved a sensitive and reliable method to confirm the presence of the virus. Under present studies, apple, peach, cherry and almond were found at a higher risk to PNRSV infection while other fruits like plum, nectarine, apricot and pear were found free from this virus, though the plants exhibited symptoms that can be related to viral etiology.
Keywords: Prunus necrotic ringspot virus; temperate fruits; DAS-ELISA